2022
DOI: 10.1021/acscatal.1c05043
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bimetallic Interactions in the Enhancement of Catalytic CO2 Reduction by a Macrocyclic Cobalt Catalyst

Abstract: The use of two metal centers in a CO 2 reduction catalyst that work together synergistically, with similar or complementary functions, can potentially lead to a significant reduction in overpotential, enhance catalytic activity and/or selectivity, and/or enable access to cascade strategies where each metal center catalyzes a different step in the conversion of CO 2 to a fuel. Here, the bimetallic reactivity of two metal centers has been identified as the primary route for the reduction of CO 2 to CO promoted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…15,16 On the other hand, carbon dioxide (CO 2 ) is the main greenhouse gas leading to serious environmental concerns. 17 Thus, converting both N 2 and CO 2 into value-added urea molecules via photocatalytic C-N coupling reaction is a feasible approach for not only achieving effective utilization of CO 2 but also mitigating environmental concerns and energy crisis. Nevertheless, the photocatalytic urea production process still suffers from extremely serious challenges.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 On the other hand, carbon dioxide (CO 2 ) is the main greenhouse gas leading to serious environmental concerns. 17 Thus, converting both N 2 and CO 2 into value-added urea molecules via photocatalytic C-N coupling reaction is a feasible approach for not only achieving effective utilization of CO 2 but also mitigating environmental concerns and energy crisis. Nevertheless, the photocatalytic urea production process still suffers from extremely serious challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Water is a weak acid in acetonitrile (p K a 38–41), and the apparent p K a of wet, CO 2 -saturated CH 3 CN is a somewhat lower 23.4 . The long-known participation of Bu 4 N + as a proton source via Hoffman degradation to tri- n -butyl amine and butene must be considered as well. ,, The computed apparent p K a of Bu 4 N + , which is present in abundance, is ∼17, but it is plausibly slow due to the poorly accessibly acidic C H 2 protons and the complication of breaking the N–C bond . The involvement of Bu 4 N + as an acid was probed by repeating the water titration CVs in the presence of 0.1 M Me 4 NPF 6 (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Electrocatalytic CO 2 reduction into valuable fuels and chemicals over dinuclear metallic complex catalysts has also attracted considerable research interest. [135][136][137][138][139] In 2018, we designed and synthesized a dinuclear Ni complex, which can serve as an electrocatalyst for the reduction of CO 2 to CO. The TON and TOF values reached as high as 4.1 Â 10 6 and 190.0 s À1 , respectively, which are 38-fold improvement of that of the corresponding mononuclear Ni complex.…”
Section: Orrmentioning
confidence: 99%
“…A series of experimental characterizations and DFT calculations revealed that a bimetallic intermediate was in situ generated from two reduced mononuclear Co species bridged by a CO 2 molecule, which is more beneficial for the CO 2 reduction to CO compared with the mononuclear pathway. 136 In addition to transition metal centers, the DMSC effect between dinuclear noble metal sites in the electrocatalytic CO 2 RR has also been studied. For example, Jurss et al designed and synthesized two anthracene-bridged dinuclear Re complexes with cis-and trans-conformers, as well as a mononuclear Re complex for electrocatalytic CO 2 reduction.…”
Section: Orrmentioning
confidence: 99%
See 1 more Smart Citation